1990
DOI: 10.1111/j.1439-0329.1990.tb01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the incidence of Rosellinia necatrix Prill. in poplars1

Abstract: Tests were carried out m controlled environments to ascertain the effects of some physical, chemical and biological characteristics of soil on the spread o\ Rosellinia necatrix and on the development of its infection in poplars. Following the results obtained, cultivation techniques have been suggested which could prevent the diffusion of the fungus or reduce the damage it causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 3 publications
(3 reference statements)
1
13
0
Order By: Relevance
“…Current evidence suggests that R. necatrix infection may be most damaging to a plant when other stress conditions, such as drought, are present (Teixeira de Sousa, 1985). Anselmi & Giorcelli (1990) in a study of factors influencing the incidence of Rosellinia infection in poplars found that R. necatrix spread rapidly on loose soil with a high sand content. They also noted that soil moisture close to field capacity encouraged mycelial spread from tree to tree but that dry conditions predisposed the trees to attack.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that R. necatrix infection may be most damaging to a plant when other stress conditions, such as drought, are present (Teixeira de Sousa, 1985). Anselmi & Giorcelli (1990) in a study of factors influencing the incidence of Rosellinia infection in poplars found that R. necatrix spread rapidly on loose soil with a high sand content. They also noted that soil moisture close to field capacity encouraged mycelial spread from tree to tree but that dry conditions predisposed the trees to attack.…”
Section: Discussionmentioning
confidence: 99%
“…The development of the R. necatrix mycelium and mycelial strands depends on temperature, oxygen, moisture and organic matter contents, pH and soil microflora. In vitro studies have shown that the optimal growth temperature is 22–24 °C; it does not grow below 4 °C or above 32 °C (Abe and Kono, 1953; Anselmi and Giorcelli, 1990; Araki, 1967; Mantell and Wheeler, 1973; Pérez‐Jiménez, 1997). Unlike most fungi, R. necatrix is not inhibited by high pH; in vitro growth occurs over a pH range of 4–9 (Makambila, 1978; Pérez‐Jiménez, 1997; Ruano‐Rosa, 2006), and growth in soil occurs over a pH range of 6–8 (Anselmi and Giorcelli, 1990; Gupta and Gupta, 1992).…”
Section: Life Cycle and Disease Symptomsmentioning
confidence: 99%
“…In vitro studies have shown that the optimal growth temperature is 22–24 °C; it does not grow below 4 °C or above 32 °C (Abe and Kono, 1953; Anselmi and Giorcelli, 1990; Araki, 1967; Mantell and Wheeler, 1973; Pérez‐Jiménez, 1997). Unlike most fungi, R. necatrix is not inhibited by high pH; in vitro growth occurs over a pH range of 4–9 (Makambila, 1978; Pérez‐Jiménez, 1997; Ruano‐Rosa, 2006), and growth in soil occurs over a pH range of 6–8 (Anselmi and Giorcelli, 1990; Gupta and Gupta, 1992). Soil moisture is the most important factor influencing the growth of the fungus and, in sandy–silt soils, the optimal growth of the mycelium is obtained at field capacity and is reduced when moisture approaches the wilting point (Anselmi and Giorcelli, 1990).…”
Section: Life Cycle and Disease Symptomsmentioning
confidence: 99%
See 2 more Smart Citations